دور الاستراتيجيات التسويقية في خلق الميزة التنافسية في القطاع المصرفي دراسة ميدانية على فروع المصرف التجاري السوري بمحافظة اللاذقية - قاسم, سامر (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يحتل مفهوم الميزة التنافسية مكاناً مهماً في الإدارة الاستراتيجية, فهي الوسيلة لأنجح التي تمكًن المنظمة من تحقيق التفوق على منافسيها باستخدام الاستراتيجية التسويقية المناسبة, بالإضافة إلى جذب الزبائن وزيادة القيمة المدركة من قبلهم وتحقيق رضاهم. يتناول البحث الحالي دور الاستراتيجيات التسويقية في خلق الميزة التنافسية في المصرف التجاري السوري بمحافظة اللاذقية, ولتحقيق أهداف البحث تمّ تصميم استبانة, وتطبيقها على عينة من العاملين في المصرف بلغت /181/ عاملاً, وبعد المناقشة والتحليل تمّ التوصل إلى النتائج الآتية: - إن الاستراتيجيات التسويقية المطبقة في المصرف التجاري السوري تمكًن المصرف من الحصول على الميزة التنافسية من خلال امتلاكه رؤية استراتيجية واضحة للتطوير سواءً أكانت خاصة بالعنصر البشري أم بالمستوى التقني التكنولوجي, وسعيه لدراسة وضع المصارف المنافسة، والارتقاء بالعمل من خلال الاتصال المستمر بالعملاء, واعتماد استراتيجية تقدم برامج ترويجية جذابة ومتناسبة مع قدرات المصرف, وتقدم الحلول الملائمة لجميع المشكلات التي يتعرض لها المصرف, كما تبين الاستراتيجية المتبعة نقاط القوة والضعف، وتدرس البيئة التسويقية الداخلية والخارجية. - تمكًن الاستراتيجيات التسويقية المطبقة في المصرف التجاري السوري من تخفيض كلفة الخدمات التي يقدمها للعملاء, ورفع مستوى جودة الخدمات المصرفية المقدّمة, والتأثير في مدى الاستجابة للعميل. The concept of competitive advantage occupies an important place in the strategic management, which is the most successful way that enables the Foundation to achieve superiority over its competitors by using the appropriate marketing strategy, as well as to attract customers and increase the value perceived by them and to achieve satisfaction. The current research addresses the role of marketing strategies in creating a competitive advantage in the Syrian Commercial Bank in Lattakia Governorate, and to achieve objectives of the research was designed to identify, and applied to a sample of employees in the bank amounted to /181/ factor, and after discussion and analysis has been reached following results: The marketing strategies applied in the Syrian Commercial Bank enables the bank to obtain a competitive advantage by having a clear strategic vision for development, and his quest to study the situation of banks, competition and improve working through ongoing contact with customers, and adopt a strategy of providing promotional programs attractive and commensurate with the capabilities of the bank, and provides appropriate solutions to all problems faced by the bank, as shown by the strategy's strengths and weaknesses and considering the marketing environment internal and external. Enable marketing strategies applied in the Commercial Bank of Syria of reducing the cost of services provided to customers, and raise the quality of banking services provided, and to influence the response to the client.